Pengaruh Return On Assets (ROA), Return On Equity (ROE) Dan Debt to Equity Ratio (DER) Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019 – 2022 - Azzahra, Meiristiani; Jayanti, Fitri Dwi; Nurani, Bulan Karima (Universitas Ngudi Waluyo, 2024)
Supply Supply and demand in the capital market have caused instability in the stock price index which has resulted in continuous rises and falls in stock prices. Investors invest capital in the hope of obtaining income from the investment they have made. This type of research is quantitative using secondary data. The population used in this research is banking companies that have gone public on the Indonesia Stock Exchange. The sampling technique in this research was carried out using a purposive sampling method, namely by selecting samples according to the criteria determined by the researcher and obtaining a research sample of 10 companies during the research year period 2019 - 2022. The data analysis method used in this research is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this research indicate that Return On Assets (ROA) has a negative effect on stock prices, Return On Equity (ROE) has a positive effect on stock prices and Debt to Equity Ratio (DER) has a negative effect on stock prices.